A Voiceprint Recognition Sensor Based on a Fully 3D‐Printed Triboelectric Nanogenerator via a One‐Step Molding Route. Issue 5 (18th February 2020) - Guo, Rui; Zhang, Hulin; Pei, Zhen; Yang, Song; Ge, Chao; Sang, Shengbo; Hao, Runfang
Abstract : The efficient preparation of energy harvesters plays a pivotal role in large‐scale applications, especially in complex or smart electronics. Currently, most of home‐made laboratorial electrical devices are fabricated by handcraft, which severely suppresses the development of triboelectric nanogenerators (TENGs). Herein, a fully 3D‐printing TENG is reported, with a PDMS tribolayer and frame directly printed on an Al electrode. The one‐step fabrication not only simplifies the manufacturing process, but also narrows differences between devices and realizes large‐scale production. The subtly fabricated TENG shows a high sensitivity to microvibration, resulting in that a voiceprint recognition sensor is demonstrated to detect human language. Because of the ingenious 3D‐printing technique, the TENG sensor can identify human words steadily and accurately. Herein, a way is paved in larger‐scale applications based on TENGs and implies more potential in artificial intelligence and future robots. Abstract : A self‐powered sensor based on fully 3D‐printing technology is fabricated. The sensor is able to recognize music rhythm and human voice by collecting the energy of sound vibration, with the characteristics of rapid prototyping and mass production. It has great potential applications in the design and manufacture of intelligent sensors.